Proyecto de desarrollo de estructuración y valoración de un programa de lealtad de clientes dirigido a un retail store - Alarcón Cabezas, Xavier Andrés (2009)
The present project seeks to create a real loyalty program for wholesale customers of a chain of clothing and footwear stores. The loyalty program seeks through segmentation strategies, customer loyalty and attachment, to stop churn rates from wholesalers, to bring back the ones who already left and new ones. Through the use of these strategies, the program looks to convert in the long run, all those wholesalers in a truly asset for the company. The most important of the categories of rewards arising from the market research are trips, white goods, business goods, technological goods and advertisements. The project is viable and one of the most important conclusions that can be highlighted is that this program will be passed on to customers who consume at retail. To implement, the company only has to correct some operational aspects prior to launch.